The Palgrave Handbook of Radical Theology (Radical Theologies and Philosophies, 2018)
The Palgrave Handbook of Radical Theology is the definitive guide to radical theology and the commencement for new directions in that field. For the first time, radical theology is addressed and assessed in a single, comprehensive volume, including introductory and historical essays for the beginner, essays on major figures and their thought, and shorter articles on various themes, concepts, and related topics. This book is a seminal work for the radical theology movement. It clarifies origins and demonstrates the exigency and utility of current figures and issues. A useful and essential guide for newcomers and veterans in the field, this volume serves as both a reference work and an introduction to omitted or forgotten topics within contemporary discussions.